Personal Hygiene Practices To Reduce The Risk Of Soil-Transmitted Helminth Infection In Farmers - Rosyidah, Kholifatur; Maulidia, Aulia; Indrasasi, Adzraa Sadira Ranu; Kurniyawan, Enggal Hadi; Afandi, Alfid Tri; Nur, Kholid Rosyidi Muhammad; Kurniawan, Dicky Endrian (International Journal of Midwifery and Health Sciences, 2024)
Backgrounds: Soil-transmitted Helminths infections have become a frequent phenomenon among farmers due to their lack of hygiene, making it easy for nematode worms to enter the body. Soil-transmitted helminths can affect nutritional status, resulting in anemia, loss of appetite, and damage to the intestines. To overcome this phenomenon, adequate personal hygiene in farmers is needed. Purpose: The purpose of this study is to analyze how personal hygiene can affect the incidence of Soil-Transmitted Helminths infection. Methods: The method used is a literature review using 10 kinds of literature from 3 sources, namely Google Scholar, PubMed, and Science Direct with a publication range from 2020-2024. Result: The results showed that some articles showed an association between personal hygiene and the incidence of soil-transmitted helminths. Good personal hygiene can prevent the entry of nematode worms into the digestive tract of the body. Besides that, some articles also showed no association between personal hygiene and soil-transmitted helminth infection. Conclusion: Adequate personal hygiene such as always using gloves and complete personal protective equipment while working, always washing hands before eating, and maintaining environmental hygiene is needed by farmers to avoid the incidence of soil-transmitted helminth infection.